If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -9) = (2x + 33) Reorder the terms: (-9 + x) = (2x + 33) Remove parenthesis around (-9 + x) -9 + x = (2x + 33) Reorder the terms: -9 + x = (33 + 2x) Remove parenthesis around (33 + 2x) -9 + x = 33 + 2x Solving -9 + x = 33 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -9 + x + -2x = 33 + 2x + -2x Combine like terms: x + -2x = -1x -9 + -1x = 33 + 2x + -2x Combine like terms: 2x + -2x = 0 -9 + -1x = 33 + 0 -9 + -1x = 33 Add '9' to each side of the equation. -9 + 9 + -1x = 33 + 9 Combine like terms: -9 + 9 = 0 0 + -1x = 33 + 9 -1x = 33 + 9 Combine like terms: 33 + 9 = 42 -1x = 42 Divide each side by '-1'. x = -42 Simplifying x = -42
| (3x+6xy+y^2)dx+(2x^2+3xy)dy=0 | | t*6-6=9 | | 2/3(3x-9)=11 | | 4a+9=2a-6 | | a*4+1=9 | | (3r+7)*2=-34 | | 12x+36=-2x | | -6n-4n=10 | | 9X^2-14X=X+6 | | 9x+1.5=4x+0.6 | | 6b+39=5b+1 | | 5(x-2)=71-4x | | 3(x-4)=36-3x | | 2y+-8x=4 | | 2x-1=119 | | 4x-5=55-8x | | 9x+2=5x+38 | | 2h-(h+12)=5h | | 1.25x+7.25=2.75 | | 363s=2162s+1 | | 2x^2+4x-9=2+x^2-2 | | (2^2x5^4/15)^4 | | Abc=4prt(forc) | | 4c-14=-2 | | 9x+1=4x+41 | | (x+58)+(x+21)=180 | | 2(2x+3)=3x+1 | | 4(n+1)=28 | | 2a=10a-5a-2 | | -2(x+6)-22=-18 | | 6n+1=6n-1 | | 5x-6=4y |